Predicting risk and outcomes for frail older adults: a protocol for an umbrella review of available frailty screening tools - Apóstolo, João Luís Alves (2015)
Review question/objective The aim of this systematic review is to comprehensively search the available literature and to summarize the best available evidence from systematic reviews in relation to published screening tools to identify pre-frailty and frailty in older adults, that is: (i) to determine their psychometric proprieties; (ii) to assess their capacity to detect pre-frail and frail conditions against established methods; and (iii) to evaluate their predictive ability. More specifically, the review will focus on the following questions: What is the reliability and validity of existing screening tools that assess pre-frailty/frailty in older patients? How sensitive and specific are pre-frailty/frailty assessment tools in identifying patients with poor prognosis? What is the ability of available pre-frailty/frailty assessment tools to predict adverse health outcomes such as functional disability, hospitalization, institutionalization, comorbidities and death?